Juror decision-making and biracial targets - Yamamoto, Susan; Maeder, Evelyn M. (Frontiers in Cognition, 2024)
Objectives This study examined potential bias against Biracial defendants using a juror decision-making paradigm. We also tested whether encouraging mock jurors not to endorse racial essentialism (belief that racial groups have inborn, immutable traits that influence behavior) would mitigate bias. Methods Canadian jury-eligible participants (N = 326) read a fabricated first-degree murder of a police officer case (involving a Black, White, or photo-morphed Black-White Biracial defendant), then made verdict decisions, completed a heuristics questionnaire, and answered racial categorization questions. Results While there were no significant effects on verdicts, those higher in heuristic thinking tended to estimate a lower percentage of European ancestry for a Biracial defendant when the defense lawyer drew attention to race. Conclusions Findings suggest that individual differences such as the tendency to rely on heuristic thinking may alter how racially ambiguous targets are perceived.